Evaluation of the Practical Implications of the ESL Curriculum at Intermediate Level - Ilyas, Muhammad Rizwan; Anjum, Rehana Yasmin; Azam, Sadia; Munir, Ayesha (Journal of Communication and Cultural Trends, 2020)
Curriculum is the basic tool used in the pedagogical process. Every education system fails if it is not developed to meet the needs of those for whom it is designed. In this research, it has been observed that the existing National Curriculum for the English Language (2006) is not fulfilling the language-based needs of the Pakistani learners. The intermediate level is the terminal level for students to discontinue education and get a job or continue learning in various advanced fields. The existing theoretical curriculum is different in terms of the practical application of English in a real-life situation. Paulo Freire’s theory of problem-posing education supports the present study. Data was collected through teacher and student questionnaires filled by intermediate students of both the public and private sectors and for the analysis of collected data CIPP model of Stufflebeam was used. For computational analysis, MS Excel was used. The results showed that learners’ creative writing skills and verbal skills are not improving satisfactorily and a gap was also found in teaching methodologies that are being currently used for teaching English. The present study is beneficial for providing the ground realities and practical needs of teachers and students in teaching and learning process. It would be helpful also for the stakeholders while designing the curriculum and syllabus.